Pelaksanaan Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Keluarga Di Kelurahan Kenanga Kota Tangerang - Anggun Nurul Chasanah; Almisar Hamid (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Individuals or groups are said to be poor if they cannot fulfill basic needs, access health and education services so that their lives are said to be less prosperous. As a form of attention from the Tangerang City government, efforts have been made to create a special program to accelerate poverty alleviation through the Family Hope Program (PKH). This research aims to describe the implementation of PKH in improving family welfare, as well as finding out the obstacles in implementing data validation and verifying the commitment of Beneficiary Families (KPM) in Kenanga Village, Tangerang City. This research uses descriptive qualitative research methods. Data collection was carried out by means of observation, interviews and documentation with informants who had been selected using pursive sampling. The research results show that the implementation of PKH in improving family welfare in Kenanga Village, Tangerang City has gone well but is not yet optimal. This is due to changes to the new system which is directly connected to DAPODIK and DUKCAPIL in the implementation process and is not based on the existing PKH implementation guidelines. The welfare level of KPM is in the Prosperous Family III category. There were problems with the absence of an initial meeting and validation for prospective KPM first by PKH assistants